A Review of Datamining Techniques in Internet of Things - Saranya, G; Subashini, M (International Journal of Computer Sciences and Engineering, 2025)
We are entering in a new era of computing technology i.e Internet of Things(IoT). IoT is a network in which all physical objects are connected to the internet through network devices or routers and exchange data. IoT allows objects to be controlled remotely across existing network infrastructure. This technique also has autonomous control feature by which any device can control without any human interaction. The enormous amount of data produced by IoT devices can be converted into knowledge using data mining techniques. Data mining will play important role in constructing smart system that provides convenient services. It is required to extract data and knowledge from the connected things. For this purpose, various data mining techniques are used. Various algorithms such as classification, clustering, association rule etc. helps to mine data. This paper represents the different Data mining techniques with IOT